Product Selectivity Controlled by Nanoporous Environments in Zeolite Crystals Enveloping Rhodium Nanoparticle Catalysts for CO2 Hydrogenation - Wang, Chengtao; Guan, Erjia; Wang, Liang; Chu, Xuefeng; Wu, Zhiyi; Zhang, Jian; Yang, Zhiyuan; Jiang, Yiwen; Zhang, Ling; Meng, Xiangju; Gates, Bruce C; Xiao, Feng-Shou (Journal of the American Chemical Society, 2019)
Supported rhodium nanoparticles (NPs) are well-known for catalyzing methanation in CO2 hydrogenation. Now we demonstrate that the selectivity in this process can be optimized for CO production by choice of molecular sieve crystals as supports. The NPs are enveloped within the crystals with controlled nanopore environments that allow tuning of the catalytic selectivity to minimize methanation and favor the reverse water–gas shift reaction. Pure silica MFI (S-1)-fixed rhodium NPs exhibited maximized CO selectivity at high CO2 conversions, whereas aluminosilicate MFI zeolite-supported rhodium NPs displayed high methane selectivity under the equivalent conditions. Strong correlations were observed between the nanoporous environment and catalytic selectivity, indicating that S-1 minimizes hydrogen spillover and favors fast desorption of CO to limit deep hydrogenation. Materials in this class appear to offer appealing opportunities for tailoring selective supported catalysts for a variety of reactions.